Predictors of paravalvular leak following implantation of the ACURATE neo transcatheter heart valve: the PREDICT PVL study - Brinkert, Miriam (Open Heart, 2020)
OBJECTIVES: Report predictors and the natural course of paravalvular leak (PVL) following implantation of the ACURATE neo transcatheter heart valve (THV). BACKGROUND: Understanding the mechanisms of PVL may help to improve patient selection, patient outcomes and the design of next-generation THVs. METHODS: A total of 30 patients (mean age 81±5 years, 47% women) undergoing transcatheter aortic valve replacement with the ACURATE neo were enrolled in the PREDICT PVL study. The effective regurgitant orifice area (EROA, in mm(2)) of PVL was assessed by transthoracic and transoesophageal echocardiography before discharge and at 6 months follow-up. RESULTS: PVL was none/trace in 10 (33%), mild in 18 (60%) and moderate in 2 (7%) patients and occurred in distinct locations with largest EROAs in the area of the left coronary cusp and its adjacent commissures. Independent predictors for EROA were implantation depth (r coefficient −1.9 mm(2) per mm implantation depth, p=0.01), leaflet calcification (6.2 mm(2) per calcification grade, p=0.03) and THV size L (7.6 mm(2) more than size S or M, p=0.01). At 6 months follow-up, EROA decreased by 29% from 13.7±9.7 mm(2) to 9.5±7.9 mm(2) (p<0.01). Patients with smaller EROAs were more likely to be in New York Heart Association class 1 than patients with larger EROAs (p<0.01). CONCLUSIONS: PVL occurred predominantly in the region of the left coronary cusp and decreased by 29% during 6 months of follow-up. Our results underscore the importance of adequate patient selection and optimal implantation depth.